PENGGUNAAN VIDIO PEMBELAJARAN DI MASA PANDEMI COVID-19 DI SMP NEGERI 2 KUANTAN HILIR SEBERANG - Maulisa, Nur Afni; Shinta, Putri; Reza, Feni Maysyah; Yuanita, Putri (Jurnal Manajemen Pendidikan, 2021)
Learning during the COVID-19 pandemic has caused problems, including poor or poor internet access, so that it becomes one of the obstacles for teaching and learning activities to take place properly. In addition, not a few students who do not get maximum learning outcomes. Both from the subject matter and assignments given by educators during the Covid-19 pandemic. The purpose of this study was to determine the learning system at SMP Negeri 2 Kuantan Hilir Seberang using learning videos. This type of research is descriptive research. Data collection techniques include observation, interviews and documentation. The subjects of this study were students of SMP Negeri 2 Kuantan Hilir Seberang. The results showed that the provision of interactive media in the form of video subject matter was able to increase students' enthusiasm in learning and students' understanding of learning materials was more optimal